2018
DOI: 10.1016/j.ecolmodel.2017.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the forest phosphorus nutrition in a southwestern Swedish forest site

Abstract: In this study, a phosphorus (P) module containing the biogeochemical P cycle has been developed and integrated into the forest ecosystem model ForSAFE. The model was able to adequately reproduce the measured soil water chemistry, tree biomass (wood and foliage), and the biomass nutrient concentrations at a spruce site in southern Sweden. Both model and measurements indicated that the site showed signs of P limitation at the time of the study, but the model predicted that it may return to an N-limited state in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 88 publications
1
28
2
Order By: Relevance
“…This can be compared with our simulated P weathering rate (down to a depth of 1 m soil depth) range of 0.009 to 0.025 g P m -2 year -1 . Both our estimations and those by Akselsson et al (2008) were 640 far lower than the 0.071 g P m -2 year -1 (0.5 m depth) reported by Yu et al (2018) for a spruce forest on Podzol soil in southern Sweden. It is important to mention that Yu et al (2018) suggested that the weathering rate they provided was an overestimation.…”
Section: Modelled P Budgets and Comparison With Published Datacontrasting
confidence: 77%
See 3 more Smart Citations
“…This can be compared with our simulated P weathering rate (down to a depth of 1 m soil depth) range of 0.009 to 0.025 g P m -2 year -1 . Both our estimations and those by Akselsson et al (2008) were 640 far lower than the 0.071 g P m -2 year -1 (0.5 m depth) reported by Yu et al (2018) for a spruce forest on Podzol soil in southern Sweden. It is important to mention that Yu et al (2018) suggested that the weathering rate they provided was an overestimation.…”
Section: Modelled P Budgets and Comparison With Published Datacontrasting
confidence: 77%
“…The modelled total plant P uptake rates in this study ranged from 0.4 to 1 g P m −2 year −1 (Table 4), which is slightly higher than the 0.5 ± 0.4 to 0.96 g P m −2 year −1 reported by 645 Johnson et al (2003) and Yanai (1992) for temperate forests, and the 0.5 g P m −2 year −1 reported for a southern Swedish forest by Yu et al (2018). One explanation for this discrepancy could be that Coup-CNP explicitly considers mycorrhizal processes related to P uptake, e.g., the presented estimates revealed that mycorrhizal fungi accounted for more than half of total plant P uptake (Table 4).…”
Section: Modelled P Budgets and Comparison With Published Datacontrasting
confidence: 60%
See 2 more Smart Citations
“…Due mainly to the relative ease of measurement and consequent ready availability of total element geochemical data on soils, indirect methods of determining quantitative soil mineralogy, such as so-called "normative" geochemical calculations have been widely used to generate mineralogical data for use in the PROFILE model. One such method is the normative "Analysis to Mineralogy" (A2M) program (Posch and Kurz, 2007) that has commonly been used in PROFILE applications (Stendahl et al, 2013;Zanchi et al, 2014;Yu et al, 2016Yu et al, , 2018Kronnäs et al, 2019). Based on a quantitative geochemical analysis of a soil sample, typically expressed in weight percent oxides, as well as on some assessment of the available minerals in the soil sample (minerals present) and their stoichiometry (chemical compositions), A2M calculates all possible mineralogical compositions for the soil sample.…”
mentioning
confidence: 99%